Republic of Poland : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that the economy of Poland has recovered from the 2012-13 slowdown. Growth accelerated to 3.4 percent in 2014, and further to 3.6 percent in the first quarter of 2015, on the back of buoyant domestic demand, supported by improving labor market and financial conditions. However, inflation has remained negative since July 2014 owing to low commodity prices and weak imported inflation. The outlook is for continued robust growth and subdued inflation amid downside risks. Economic expansion is expected to continue, with growth projected at 3.5 percent in 2015 and over the medium term.